Practical systems biology [ - Grierson, Claire; Hetherington, A. M. (Experimental biology reviews, 2008)
Practical Systems Biology provides a detailed overview of the different approaches used in this relatively new discipline, integrating bioinformatics, genomics, proteomics and metabolomics. Various areas of research are also discussed, including the use of computational models of biological processes, and post-genomic research